Gestão do patrimônio documental: elaboração do vocabulário controlado para organizar e acessar informações arquivísticas - Ilha, Rita Medianeira (2013)
The study of the vocabulary used to name the Federal University of Santa Maria (UFSM) functions and activities is the one presented in this research aiming at controlling the vocabulary and, to build a controlled vocabulary as a means of standardization to improve the searching and access of documents. This is an applied research with a qualitative approach that seeks to develop the knowledge making it possible to understand and transform the reality regarding the presented topic. The work was structured considering the documents classification plan that already existed, which were used to survey the terms used to name classes, subclasses and document types. The survey made it possible to identify and analyze the terminological differences and, to apply the vocabulary control to both micro and macro vocabulary control procedures. The result was the development of a Controlled Vocabulary, disposed in alphabetical order, containing the adopted and not adopted terms, serving as a remitting. The purpose is to qualify the UFSM Archival System with regard to documents search and access.